2011
DOI: 10.1093/treephys/tpr093
|View full text |Cite
|
Sign up to set email alerts
|

The long way down--are carbon and oxygen isotope signals in the tree ring uncoupled from canopy physiological processes?

Abstract: The carbon (δ(13)C) and oxygen (δ(18)O) stable isotope composition is widely used to obtain information on the linkages between environmental drivers and tree physiology over various time scales. The tree-ring archive can especially be exploited to reconstruct inter- and intra-annual variation of both climate and physiology. There is, however, a lack of information on the processes potentially affecting δ(13)C and δ(18)O on their way from assimilation in the leaf to the tree ring. As a consequence, the aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
122
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(129 citation statements)
references
References 71 publications
4
122
3
Order By: Relevance
“…Latewood sections from a given species, a given year, and a given stand were bulked and analyzed for δ 13 C with a mass spectrometer. By selecting only the latewood, whose δ 13 C mainly characterizes the functioning of the trees during the second part of the growing season, we avoided potential effects related to the remobilization of stored photosynthates from the previous growing season (26) or to a favorable spring climate.…”
Section: Methodsmentioning
confidence: 99%
“…Latewood sections from a given species, a given year, and a given stand were bulked and analyzed for δ 13 C with a mass spectrometer. By selecting only the latewood, whose δ 13 C mainly characterizes the functioning of the trees during the second part of the growing season, we avoided potential effects related to the remobilization of stored photosynthates from the previous growing season (26) or to a favorable spring climate.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, the lack of change in P. ponderosa foliar d 13 C could also be due to 2012 foliage being formed from carbon stores from previous years. Both Kagawa et al (2006) and Offermann et al (2011) found that stored carbohydrates assimilated in previous years are used in current year foliage formation. This process may be more pronounced during drought and pine species may rely heavily on carbon reserves during drought seasons for radial growth (Oberhuber et al 2011).…”
Section: How Does Intrinsic Iwue Respond To Drought?mentioning
confidence: 99%
“…2.3), the potential limitations of using the bulk isotope signature need to be kept in mind and sampling strategies need to be adapted. For trees, the intra-annual analysis of tree ring, whole wood or cellulose can provide a tool to study periods during the growing season when the isotopic signature in this archive is directly coupled to leaf physiology (Helle and Schleser, 2004;Offermann et al, 2011).…”
Section: Interpretation Of 13 C B and 18 O B In Relation To Leaf Traitsmentioning
confidence: 99%